2020
DOI: 10.3389/fpsyt.2020.00177
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Five Facets of Mindfulness in a Mindfulness-Based Psychoeducation Intervention for People With Recent-Onset Psychosis on Mental and Psychosocial Health Outcomes

Abstract: Objective: This study aimed to examine how five facets of mindfulness may be associated with the changes in psychotic patients' health outcomes after participating in a mindfulness-based psychoeducation group (MBPEG) program.Methods: Longitudinal follow-up data from two pragmatic randomized controlled trials of MBPEG for psychotic patients were used for this study. A total of 124 patients who completed the MBPEG program were included in this analysis. Patient outcomes (psychotic symptoms, functioning, insight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 56 publications
(78 reference statements)
1
15
0
1
Order By: Relevance
“…Moreover, although the included studies in this review suggested a number of strategies in addressing psychological issues among Chinese patients and healthcare staff, studies on the effectiveness of such interventional strategies specifically on Chinese patients and healthcare staff appear to be lacking. Further, with certain interventions such as yoga, cognitive behavioural therapies, and mindfulness-based interventions having shown to be effective in addressing psychological issues such as anxiety and depression [ 77 , 78 , 79 , 80 ], research efforts may also be directed towards the evaluation of the effectiveness of such interventions in reducing these psychological symptoms among the aforementioned Chinese subjects. Indeed, more research on the feasibility and effectiveness of these interventional strategies would be required to provide the evidence base in making a case for the development of the suggested strategies for implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although the included studies in this review suggested a number of strategies in addressing psychological issues among Chinese patients and healthcare staff, studies on the effectiveness of such interventional strategies specifically on Chinese patients and healthcare staff appear to be lacking. Further, with certain interventions such as yoga, cognitive behavioural therapies, and mindfulness-based interventions having shown to be effective in addressing psychological issues such as anxiety and depression [ 77 , 78 , 79 , 80 ], research efforts may also be directed towards the evaluation of the effectiveness of such interventions in reducing these psychological symptoms among the aforementioned Chinese subjects. Indeed, more research on the feasibility and effectiveness of these interventional strategies would be required to provide the evidence base in making a case for the development of the suggested strategies for implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several longitudinal studies conducted during MBIs pointed to Acting with Awareness as a facet of mindfulness that predicted beneficial improvement in mindfulness and mental health over time (e.g. 23 , 49 , 50 ). Although our cross-sectional design precludes any strong inference regarding the temporal dynamics of the mindfulness facets per se, the results invite the hypothesis that Acting with Awareness might be an especially potent constituting feature of mindfulness.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to MBI, interventions with the aim of improving living environments and behavior (e.g., education, exercise, diet, sleep) were associated with changes in DNA methylation profiles [ 148 , 149 ]. Furthermore, elements of MBI have been combined with existing cognitive and psychological interventions [ 150 , 151 ]. Changes were observed in the DNA methylation profiles in response to cognitive behavioral therapy and social support [ 152 , 153 ].…”
Section: Epigenetic Changes Induced By Mind–body Intervention and mentioning
confidence: 99%